Pembangunan Sektor Pertanian Sebagai Basis Pertumbuhan Ekonomi Pedesaan : (Kajian Kepustakaan) - Damianus Tola (Program Studi Pendidikan Ekonomi, Universitas Flores, 2016)
Ende has enormous agricultural potential views of the undertaking in the agricultural sector. This article would reveal the agricultural sector sustain rural economic growth base. In promoting development, local government menentapkan strategy for improving the quality of human resources, through formal and informal education, which is a development policy with the aim of expanding employment opportunities for the people to be tried either in agriculture, industry and engaged in the services sector. When everything is moving forward at a rapid pace, it will be followed by an increase in Gross Domestic Product (GDP) and economic growth in the region will be better. This potential allows Ende can boost development in agriculture. From the data (GDP) found that: the undertaking (1) Plant material feeding, (2) Plant & Farming, (3) Ranch (4) Forestry (5) Fisheries, in Ende is still dominated by plants to eat from the year 2013 by 12,45, the year 2014 amounted to 12.16 and 2015 amounted to 11.94 of the most prominent businesses that eat plants.